Analisis Etika Bisnis Bedasarkan Pemikiran Al-Imam Ghazali: Studi Kasus Pada Perusahaan Mineral Water Dan MBS Bakery - Mohammad Majduddin (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2023)
This research aims to investigate the implementation of business ethics in Mineral Water Companies by referring to the principles that emerged in the thoughts of Al-Imam Ghazali. The case study method is used to gain an in-depth understanding of the business practices, policies and values adopted by the company. The research subjects involved mineral water companies and MBS Bakery, selected based on their good reputation in business practices and commitment to ethical values. Data was collected through interviews, observation and document analysis. Data analysis was carried out qualitatively with a thematic and comparative approach. The research results show that the Mineral Water Company consistently applies the principles of business ethics, including honesty, justice and social responsibility. The implications of this research show that the application of business ethics can be a strategic force to improve company performance, increase consumer trust, and strengthen the company's image regarding environmental sustainability. Recommendations include improved employee training programs, marketing strategies more focused on ethical values, and increased environmental sustainability efforts. Thus, this research not only provides in-depth insight into the business practices of Mineral Water Company but also confirms the importance of business ethics in achieving long-term sustainable success.